2017
DOI: 10.1016/j.celrep.2017.09.097
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Microbial Communities Trigger Colitis Development upon Intestinal Barrier Damage via Innate or Adaptive Immune Cells

Abstract: SummaryInflammatory bowel disease comprises a group of heterogeneous diseases characterized by chronic and relapsing mucosal inflammation. Alterations in microbiota composition have been proposed to contribute to disease development, but no uniform signatures have yet been identified. Here, we compare the ability of a diverse set of microbial communities to exacerbate intestinal inflammation after chemical damage to the intestinal barrier. Strikingly, genetically identical wild-type mice differing only in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 48 publications
7
92
0
Order By: Relevance
“…Also, the FMD treatment in the current study lasts 4 days and is repeated multiple times, compared to the single, water-only fasting lasting between 36–48 hours in previous studies. Notably, Paraprevotellaceae, associated with water-only fasting but not FMD treatment, has been previously regarded as pro-inflammatory in the context of IBD, with one study finding it to be especially enriched in mice with severe colitis (Roy et al, 2017). Another study also found Paraprevotellaceae abundance increased in rats with increased pro-inflammatory cytokines, such as IL-13, in colonic tissue (Shatzkes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the FMD treatment in the current study lasts 4 days and is repeated multiple times, compared to the single, water-only fasting lasting between 36–48 hours in previous studies. Notably, Paraprevotellaceae, associated with water-only fasting but not FMD treatment, has been previously regarded as pro-inflammatory in the context of IBD, with one study finding it to be especially enriched in mice with severe colitis (Roy et al, 2017). Another study also found Paraprevotellaceae abundance increased in rats with increased pro-inflammatory cytokines, such as IL-13, in colonic tissue (Shatzkes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We also provide a multi-sample mouse gut data set for software developers to benchmark against. For 64 16S rRNA samples from the mouse gut [17], we simulated 5 Gb of Illumina and PacBio reads each. The mice were obtained from 12 different vendors and the samples characterized by 16S V4 amplicon sequencing (OTU mapping file in the supplement).…”
Section: Simulating Environment-specific Data Setsmentioning
confidence: 99%
“…We demonstrate the usability and utility of CAMISIM with several applications. We generated complex, multi-replicate benchmark data sets from taxonomic profiles of human and mouse gut microbiomes [1,17]. We also simulated thousands of small "minimally challenging metagenomes" to characterize the effect of varying sequencing coverage, evolutionary divergence of genomes, and sequencing error profiles on the popular MEGAHIT [18] and metaSPAdes [19] assemblers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported on the link between neutrophils and the gut microbiome [18][19][20][21]. A study by Li et al isolated peripheral neutrophils from participants with the aim of identifying and characterising neutrophil-associated microbiomes [22].…”
Section: Cells; T Cells: T Lymphocytes; B Cells: Bmentioning
confidence: 99%